CHIPIC: An Efficient Code for Electromagnetic PIC Modeling and Simulation - Zhou, Jun; Liu, Dagang; Liao, Chen; Li, Zhenghao (IEEE transactions on plasma science, 2009)
Computer-aided highly efficient electromagnetic particle-in-cell (PIC) (CHIPIC) code, developed at the University of Electronic Science and Technology of China, is a fully computer-aided code which combines modeling, calculations, and analysis with an integrated environment. CHIPIC is specifically designed for efficient modeling and simulation. CHIPIC includes a computer-aided design (CAD) system and a physical kernel. The CAD system is designed based on the common flowchart of PIC simulation to provide efficient modeling and analysis, and the physical kernel is developed to provide fast and accurate calculations. The physical kernel can run on a single processor or in parallel mode. When it runs in parallel mode, the message-pass interface and open specifications for multiprocessing are adopted. The validity of this electromagnetic PIC code is proved by simulating a magnetically insulated transmission-line-oscillator tube.